Дослідження дисперсності розпилювання крапель палива факелу бензинової форсунки - Підгорний, М. В.; Кузьменко, С. О.; Роздобудько, Є. О. (НТУ "ХПІ", 2015)
Тенденції до збільшення потужності двигуна, зниження витрат палива, поліпшенню екологічних показників привели до необхідності більш точного дозування палива та оптимізації приготування паливно-повітряної суміші.Саме тому в роботі розроблено методику експериментальних досліджень, виготовлено стенд для досліджень форсунок сучасних автомобілів та проведено необхідну кількість дослідів відповідно до досліджень факела розпилювання паливної суміші.Розв’язано наступні задачі:отримано математичну модель досліджуваного об'єкту у вигляді рівняння множинної регресії; проведено експеримент; подано опис результатів експериментальних досліджень;визначено умови роботи форсунки на яких факел є максимальний.

The trend to wards increased engine power, lower fuel consumption, improve environmental performance have led to the need for more precise do sage of fuel optimizing and cooking fuel-airmixture. That is why the work the method of experimental research, made a stand for research injectors modern cars and the required number of experiments conducted according to research cutting torch fuel mixture.On the stand manufactured conducted the required number of experiments that meets planning matrix, there sults presented in the form of pictures and graph sand optimal angles pray nozzlepetrol. Toachieve the purpose of the investigation they will be solved next tasks: 1. Analysis of existing designs of gasoline nozzles. 2. Preplanning of experimental technique of investigations. 3. Experimental conducting. 4. Description of experimental results. The paper gives a detailed analysis of existing gasoline injectionsystems. It was preplanned the experimental technique of investigation, produced the necessary test bench. The required number of experiments due to making of researches is conducted.It specified conditions of maximum torch running of the nozzle.
The study of dispersion of droplets of fuel spray plume petrol injectors
Keywords: схема управління форсунками; методика експерименту; параметри роботи двигуна; автомобілі; nozzle injector control circuit; experimental procedure; parameter sof the engine; torch nozzle